GUI Design with C# Windows Form Application for MPP Estimation - Gündoğdu, Fatih; Gündoğdu, Ahmet; Çelikel, Reşat (Hibetullah KILIÇ, 2025)
In this study, an interactive graphical user interface was developed to both facilitate the performance analysis of photovoltaic systems and serve educational purposes. The aim was to visualize how the maximum power point of a PV panel changes based on user-defined parameters. The interface was designed using the C# programming language and Windows Forms application. Users can enter key parameters such as ambient temperature and irradiance value via the keyboard. In the background, a mathematical model of the PV panel is executed to calculate the maximum power points for different temperature and irradiance conditions, and the results are displayed on the Graphical User Interface screen. The simulations conducted have shown that the user-friendly interface significantly simplifies the understanding of complex PV panel behaviours. The effects of varying atmospheric conditions on the location of the maximum power point and the overall efficiency of the panel can be clearly observed. The developed C# -based interface is considered an effective, low-cost, and accessible tool for teaching the fundamental principles of photovoltaic systems and enabling quick performance analysis.

Bu çalışmada, fotovoltaik sistemlerin hem performans analizini kolaylaştıracak hem de eğitim amaçlı kullanılabilecek etkileşimli bir grafiksel kullanıcı arayüzü geliştirilmiştir. PV panelin maksimum güç noktasının izlenmesi, kullanıcıdan alınan parametrelere dayalı olarak nasıl değiştiğinin görselleştirilmesi hedeflenmiştir. Geliştirilen arayüz, C# programlama dili ve Windows Forms kullanılarak tasarlanmıştır. Kullanıcı, ortam sıcaklığı, ışınım değeri gibi temel parametreleri klavye aracılığı ile giriş yapar. Arka planda PV panelin matematiksel modeli işletilerek, farklı sıcaklık ve ışınım değerleri için maximum güç noktaları hesaplanır ve Graphical User Interface ekranında yazdırılır. Yapılan simülasyonlar, kullanıcı dostu arayüzün karmaşık PV panel davranışlarının anlaşılmasını önemli ölçüde kolaylaştırdığını göstermiştir. Değişken atmosferik koşulların, maximum güç noktasının konumu ve panelin genel verimliliği üzerindeki etkileri net bir şekilde gözlemlenebilmektedir. Geliştirilen C# tabanlı arayüz, fotovoltaik sistemlerin temel prensiplerinin öğretilmesi ve hızlı bir şekilde performans analizinin yapılması için etkili, düşük maliyetli ve erişilebilir bir araç olarak değerlendirilmektedir.
MPP Tahmini için C# Windows Form Uygulaması ile GUI Tasarımı
Keywords: Computer Software; Bilgisayar Yazılımı; Electrical Energy Generation (Incl. Renewables; Excl. Photovoltaics); Elektrik Enerjisi Üretimi (Yenilenebilir Kaynaklar Dahil; Fotovoltaikler Hariç)